2019
DOI: 10.3389/fnins.2019.00158
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Roles of Teneurins in Zebrafish

Abstract: The teneurins, also known as Ten-m/Odz, are highly conserved type II transmembrane glycoproteins widely expressed throughout the nervous system. Functioning as dimers, these large cell-surface adhesion proteins play a key role in regulating neurodevelopmental processes such as axon targeting, synaptogenesis and neuronal wiring. Synaptic specificity is driven by molecular interactions, which can occur either in a trans-homophilic manner between teneurins or through a trans-heterophilic interaction across the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…tenm2 is a gene expressed early on during zebrafish embryogenesis as well as in cichlid brain and embryo (Supplementary Fig. 11h), and is involved in neurodevelopment and neuron migration-related cell signalling 56 . This 2.7kbp-long DMR is completely unmethylated in the algae-eating rock-dweller Petrotilapia genalutea (almost 80% reduction of methylation overall compared to the other species) and may mediate species-specific adaptive phenotypic plasticity related to synapse formation and neuronal networks.…”
Section: Resultsmentioning
confidence: 99%
“…tenm2 is a gene expressed early on during zebrafish embryogenesis as well as in cichlid brain and embryo (Supplementary Fig. 11h), and is involved in neurodevelopment and neuron migration-related cell signalling 56 . This 2.7kbp-long DMR is completely unmethylated in the algae-eating rock-dweller Petrotilapia genalutea (almost 80% reduction of methylation overall compared to the other species) and may mediate species-specific adaptive phenotypic plasticity related to synapse formation and neuronal networks.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that NEDD4 acts as an E3 ligase and regulates the embryonic development and growth of animals (proliferation, autophagy and differentiation of multiple malignancies) [ 35 ]. The TENM3 gene encodes highly conservative transmembrane glycoproteins of type II that are widely expressed in the nervous system and play a key role in regulating the development of the nervous system [ 36 ]. Feldman et al [ 37 ] proposed that mutations in the TENM3 gene in humans and mice lead to a slowdown of chondrogenes.…”
Section: Discussionmentioning
confidence: 99%
“…In the chick visual system, for example, Ten-m1 and Ten-m2 were found to be differentially expressed by the tectofugal and thalamofugal pathways, respectively (Rubin et al, 1999, 2002). Dynamic and differential, but partially overlapping, expression patterns have also been observed in the nervous system of zebrafish, with particularly strong expression of Ten-m3 and Ten-m4 (Mieda et al, 1999; Cheung et al, 2019). In this species, expression of Ten-m3 in the amacrine and ganglion cells of the developing retina is important for the formation of intraretinal circuitry (Antinucci et al, 2013, 2016).…”
Section: Topographically Corresponding Gradients Mediate Precise Matcmentioning
confidence: 97%
“…While the Ten-ms clearly play an important role in the formation of binocular visual circuits in mice, it should be pointed out that they are also expressed in the visual pathway of zebrafish and chicks (Rubin et al, 1999, 2002; Antinucci et al, 2013; Cheung et al, 2019), species which have little or no ipsilateral retinal projection. In zebrafish, which have entirely crossed retinal projections and lack binocular overlap, Ten-m3 has been shown to contribute to the specification of RGC connectivity and function (Antinucci et al, 2013, 2016), consistent with its role as a homophilic adhesion molecule.…”
Section: Functional Impacts From Loss Of Teneurin Functionmentioning
confidence: 99%
See 1 more Smart Citation